MODUS DAN FAKTOR PENYEBAB MARAKNYA KASUS PEKERJA MIGRAN INDONESIA (PMI) ILEGAL DI KABUPATEN LUMAJANG - Fathullah, Kholidazia El Hamzah; Ma’shum, Ahmad Djazim (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstract The low level of wages in the country is related to the limited number of jobs available, making people prefer to work abroad. Most Indonesian Migrant Workers (PMI) choose illegal routes. In many cases of illegal migration, both in the context of internal migration and international migration, the role of "taikong" or labor brokers is very important. As happened in Lumajang Regency, in November 2023, it was recorded in the Lumajang District Court's Case Tracking Information System (SIPP) that there were 6 cases of the Crime of Human Trafficking (TPPO) committed by taikong or brokers in sending and placing PMI illegally abroad. . The aim of this research is to analyze the Taikong or Broker Mode in Lumajang Regency in the Illegal Placement of Indonesian Migrant Workers (PMI) Abroad and to analyze the factors that cause Indonesian Migrant Workers (PMI) to choose illegal methods. This research uses empirical legal research with a juridical-sociological approach. Keyword : Modus, the Illegal Placement of Indonesian Migrant Workers, the Crime of Human Trafficking